THE EFFECT OF SONG MEDIA TO STUDENTS’ LEARNING MOTIVATION IN VII CLASS ON CHARACTERISTICS OF LIVING THINGS MATERIAL - 'Aini, Kurratul; Samiha, Yulia Tri; Arya, Wely Julita (Al 'Ilmi : Jurnal Pendidikan MIPA, 2015)
This research aims to determine the influence of song media against student learning motivation. This research was conducted at Palembang Islamic Junior High School on June 2017. The research method used quasi experimental design of Non - equivalent control group design. The population in this research is the students of class VII consisting of 2 classes with the number of each class on average 30 students, with class VII B as the experimental class and VII A as the control class, sampling is done by saturated sampling technique . Learning media used media song. Data collection is using questionnaire of students learning motivation. The results of the analysis of the number of questionnaires obtained significance value of 0.000 this means the value of significance <0,05 or 0,000 <0,05. This indicates that H0 is rejected and Ha accepted so the hypothesis states that the song media has an effect on learning motivation . Keywords : learning media, song media, motivation to learn, the characteristics of living things